PENGARUH BASIS SALEP HIDROKARBON DAN BASIS SALEP SERAP TERHADAP FORMULASI SALEP SARANG BURUNG WALET PUTIH (Aerodramus fuciphagus) - Dita Ayulia Dwi Sandi; Yaumi Musfirah (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Swiftlet nest is edible bird’s nest (EBN). Edible bird’s nest contain EGF (Epidermal Growth Factor) that has a role in skin cell regeneration. This research aims to find out the effect of the hydrocarbon and absorption bases on the edible bird’s nest ointment (Aerodramus fuciphagus) from the physical character of each ointment. The edible bird’s nest ointment made into two formula with hydrocarbonand absorption bases. Each ointment tested of the physical characteristics include organoleptic test, homogenity test, pH test, spreading test, sticky test, and viscosity test. The data obtained was analyzed statistically using T Independent Test. The result showed that there was affect the hydrocarbon and absorption bases to the physical characteristics of edible bird’s nest ointment include spreadability (P 0,011), sticky (P 0,020), and viscosity, but there was not affect to organoleptic, homogenity and pH of edible white bird’s nest ointment (Aerodramus fuciphagus).